How Does Thymus Infection by Coxsackievirus Contribute to the Pathogenesis of Type 1 Diabetes? - Michaux, Hélène; Martens, Henri; Jaïdane, Hela; Halouani, Aymen; Hober, Didier; Geenen, Vincent (Frontiers in Immunology, 2015)
Through synthesis and presentation of neuroendocrine self-antigens by major histocompatibility complex (MHC) proteins, thymic epithelial cells (TECs) play a crucial role in programming central immune self-tolerance to neuroendocrine functions. Insulin-like growth factor-2 (IGF-2) is the dominant gene/polypeptide of the insulin family that is expressed in TECs from different animal species and humans. Igf2 transcription is defective in the thymus of diabetes-prone Bio-Breeding (BB) rats, and tolerance to insulin is severely decreased in Igf2-/- mice. For more than 15 years now, our group is investigating the hypothesis that, besides a pancreotropic action, infection by coxsackievirus B4 (CV-B4) could implicate the thymus as well, and interfere with the intrathymic programming of central tolerance to the insulin family and secondarily to insulin-secreting islet β cells. In this perspective, we have demonstrated that a productive infection of the thymus occurs after oral CV-B4 inoculation of mice. Moreover, our most recent data have demonstrated that CV-B4 infection of a murine medullary (m) TEC line induces a significant decrease in Igf2 expression and IGF-2 production. In these conditions, Igf1 expression was much less affected by CV-B4 infection, while Ins2 transcription was not detected in this cell line. Through the inhibition of Igf2 expression in TECs, CV-B4 infection could lead to a breakdown of central immune tolerance to the insulin family and promote an autoimmune response against insulin-secreting islet β cells. Our major research objective now is to understand the molecular mechanisms by which CV-B4 infection of TECs leads to a major decrease in Igf2 expression in these cells.